PROFIL KADAR GLUKOSA DARAH PASIEN DIABETES MELLITUS TIPE 2 YANG MENGGUNAKAN ATORVASTATIN 20 MG DI RUMAH SAKIT MADANI, ANUTAPURA DAN UNDATA PERIODE 2015-2019 - Lestari, Widya; Mukaddas, Alwiyah (Fakultas Farmasi UMI, 2020)
Atorvastatin is one of the lipophilic statins that can cause diabetes through some mechanisms, such as liphophilic properties, it’s activities to insulin secretion, insulin signaling, and adiponectin levels. The purpose of this research is to know demographic data, profile of when blood sugar levels, and the time needed for atorvastatin to increase blood sugar when type 2 diabetes mellitus patients use atorvastatin for 20 mg. This research is observational descriptive research with retrospective data collection approach by looking at the usage of atorvastatin, with total samples 22 patients obtained from medical record data at Madani hospital, Anutapura and Undata in Palu in the period of 2015-2019. This research result shows that the demographic data of the average age of type 2 diabetes mellitus patients in which complications of dysplidemia that uses atorvastatin for 20 mg are in the age of 45-56 years old, female gender (57.14%), with the last education of Senior High School (38.09%) and occupation as Government Employees (33.33%), the time needed for atorvastatin 20 mg to increase blood sugar is 2 months (the difference is 26.38 mg/dl; percentage 19.52%) and the percentage of highest blood sugar increase is one year, which is 93.91%.